PREVALENCE OF GASTROINTESTINAL PARASITES IN BUFFALOES IN THE STATE OF PARAÍBA AND THE FIRST REPORT OF Cystoisospora spp. IN BUFFALOES IN BRAZIL - VILELA, V. L. R.; FEITOSA, T. F.; BRASIL, A. W. L.; PARENTONI, R. N.; BEZERRA, R. A.; AZEVÊDO, S. S. (Ars Veterinaria, 2017)
The aims of this study were to determine the prevalence of gastrointestinal parasites in buffaloes in the state of Paraíba, and to identify the risk factors associated with parasitic infection. The study involved 127 randomly selected buffaloes from 14 farms. Fecal Egg Count (FEC), fecal culture, and centrifugation-flotation in sucrose solution were performed. The prevalence of gastrointestinal parasites was 24.4% (31/127). ). Among the infected animals, 8.6% (11/127) had helminths, 13.4% (17/127) had enteric protozoa, and 2.3% (3/127) had both. The helminth genus identified most frequently in fecal culture was Haemonchus spp. (59%), followed by Trichostrongylus spp. (34%), and Oesophagostomum spp. (7%). Eimeria spp. were present in 11.8% (15/127), Giardia sp. in 2.4% (3/127), and Cystoisospora spp. in 1.6% (2/127) of the animals. Animal purchase from livestock auctions/fairs was identified as a risk factor for gastrointestinal parasites (odds ratio = 25.44; 95% CI = 2.,17 – 297.68; P = 0.010). Although approximately 25% of buffaloes in the state of Paraíba were infected with gastrointestinal parasites, the intensity of infection was low. To the best of our knowledge, this is the first study reporting the occurrence of Cystoisospora spp. in these animals in Brazil.